Investigating the corrosion behavior of hot-dip galvanized Zn and Zn-10Al coatings on carbon steel without top coating in chloride-rich immersion environments - Agus Solehudin; Haipan Salam; Risti Ragadhita; Muhammad Irfansyah Maulana (Universitas Muhammadiyah Magelang, 2025)
This study investigates the corrosion resistance, surface hardness, morphological structure, and predicted lifetime of carbon steel coated with pure zinc (Zn) and zinc aluminum alloy (ZnAl) in chloride rich environments. Coatings were applied by hot dip galvanizing, and characterized using Field Emission Scanning Electron Microscopy Energy Dispersive X-ray Spectroscopy (FESEM-EDS), Vickers hardness testing, and salt spray testing. Before exposure, both coatings confirmed homogeneity with smooth, topographically uniform surfaces, and no macroscopic defects. ZnAl coatings also delivered superior hardness compared to pure Zn and uncoated steel. After exposure, ZnAl maintained smoother, more stable surfaces with smaller and fewer pitting defects, whereas pure Zn suffered medium to severe damage. Pure Zn coatings showed fluctuating corrosion behavior with an average rate of 7.8944 µm/year, while ZnAl coatings exhibited minimal fluctuations within ±0.1 µm/year, indicating high resistance to chloride concentration. Predicted lifetime ranged from 3.7 to 5.5 years for pure Zn (average 4.7 years) and 5.9 to 6.5 years for ZnAl (average 6.2 years). Despite being thinner, ZnAl provided superior corrosion protection and structural stability. These findings indicate that ZnAl alloy coatings provide superior corrosion protection, structural stability, and mechanical performance for carbon steel in chloride rich environments.